2014
DOI: 10.2169/internalmedicine.53.1599
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Diffuse Cutaneous Systemic Sclerosis Complicated by Antineutrophil-cytoplasmic Antibody-associated Vasculitis Exhibiting Honeycomb Lung without Volume Loss

Abstract: We herein report the case of a 72-year-old woman with diffuse cutaneous systemic sclerosis (SSc) complicated by antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis who exhibited honeycomb lung without volume loss. On admission, chest computed tomography (CT) revealed honeycomb lung without volume loss in addition to increased density of the partition walls. A renal biopsy revealed global sclerosis and cellular crescent formation. Mononeuritis multiple subsequently occurred, and steroid pulse thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The clinical significance of ANCA in SSc patients who do not manifest AAV is controversial. An association between ANCA in SSc and ILD has been suggested [12, 20–22]. However, this has not been consistently reported in all case series [15].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical significance of ANCA in SSc patients who do not manifest AAV is controversial. An association between ANCA in SSc and ILD has been suggested [12, 20–22]. However, this has not been consistently reported in all case series [15].…”
Section: Introductionmentioning
confidence: 99%
“…We identified six papers describing the clinical features of 12 SSc patients with ANCA‐associated neuropathy (Table 1). 2,3,5–8 In all the reported cases, the SSc diagnosis preceded the ANCA‐associated neuropathy diagnosis. Positive results for anti‐Scl‐70 antibody were observed in five patients (5/12).…”
Section: Discussionmentioning
confidence: 98%
“…reported a case of AAV in 72-year-old lady with diffuse cutaneous SSc with cellular crescent on renal biopsy and mononeuritis multiple. [ 2 ] In another study with 12 patients of systemic vasculitis and associated SSc, AAV was found in nine patients. Renal limited vasculitis was found in only two out of these nine patients.…”
mentioning
confidence: 99%